Phase and thermodynamics-informed predictive model for laser beam additive manufacturing of a multi-principal element alloy - Das, Chayan; Sreeramagiri, Praveen; Balasubramanian, Ganesh (Frontiers in Metals and Alloys, 2023)
The complex solidification cycles experienced by multi-principal element alloys (MPEAs) during laser based additive manufacturing (LBAM), often leads to structural defects, affecting the build quality. The underlying thermal processes and phase transformations are a function of the process parameters employed. With a moving Gaussian heat source to mimic LBAM, and leveraging material thermodynamics guidelines from CALPHAD, we estimate the temperature-dependent thermal properties, phase fractions and melt-pool geometry using an experimentally-validated computational fluid dynamics model. The results substantiate that the peak temperatures are inversely correlated to the scan speeds, and the melt-pool dimensions can assist in the predictive selection of process parameters such as hatch distance and layer thickness. A relatively low cooling rate recorded during the process is ascribed to the pre-heating of the substrate to ensure printability of the alloy.